2016
DOI: 10.1186/s12877-016-0364-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of the interRAI home care frailty scale

Abstract: BackgroundThe concept of frailty, a relative state of weakness reflecting multiple functional and health domains, continues to receive attention within the geriatrics field. It offers a summary of key personal characteristics, providing perspective on an individual’s life course.There have been multiple attempts to measure frailty, some focusing on physiologic losses, others on specific diseases, disabilities or health deficits. Recently, multidimensional approaches to measuring frailty have included cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Participants were most commonly sampled from the Netherlands (29 of 95 studies) 27,58–60,66,74,75,82,84–90,93,94,96,99,100,105,109,111–113,123–126 . The cohorts were predominantly community based generally older adult populations (51 of 95) 3,9,27,40,44,46,48,54–56,58–60,65,67,68,72,74,75,77,79,80,82–86,88,93–97,101,103,104,106,107,109,116,117,121–130 . Only one of the 95 cohorts consisted of “psychogeriatric patients” (80.8% diagnosed with dementia, 5% depression, 11% unspecified, 3% no mental disorder) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were most commonly sampled from the Netherlands (29 of 95 studies) 27,58–60,66,74,75,82,84–90,93,94,96,99,100,105,109,111–113,123–126 . The cohorts were predominantly community based generally older adult populations (51 of 95) 3,9,27,40,44,46,48,54–56,58–60,65,67,68,72,74,75,77,79,80,82–86,88,93–97,101,103,104,106,107,109,116,117,121–130 . Only one of the 95 cohorts consisted of “psychogeriatric patients” (80.8% diagnosed with dementia, 5% depression, 11% unspecified, 3% no mental disorder) .…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesis testing had the greatest number of fair ratings (65 of 70). A total of 42 of 95 studies had at least one aspect of methodological quality rated as poor 41,44–48,50,51,55,56,58,59,61,63,66–68,74,76–78,80,82,84–86,89,96–98,102,103,106,109,110,113,116,117,119,124,127,128 . Criterion validity had the greatest number of poor ratings (30 of 42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies convincingly demonstrated that an FI can be derived from data collected with unified instruments from the interRAI suite either with the interRAI Acute Care [ 17 ], interRAI Nursing Homes [ 18 ], or interRAI Home Care [ 19 ]. Aside from FI derivations, scales assessing frailty have also been proposed; among them, the Frailty Scale [ 20 ] built from the interRAI Home Care and the FRAIL-NH scale [ 21 , 22 ] elaborated on the interRAI Nursing Home. The former operationalizes frailty as an accumulation of deficit [ 13 ], and the latter relies on the phenotype model of frailty [ 23 ], which assigns individuals to “robust”, “pre-frail”, and “frail” categories based on a restricted number of variables assessing predefined physiological resources.…”
Section: Introductionmentioning
confidence: 99%
“…Utilising the frailty index methodology, researchers have developed and tested an operationalised frailty model in different sectors, including acute care(305) and care home (306). Although these two frailty indices were not entirely similar, it is theoretically possible to measure frailty across a patient journey.…”
Section: Is a Universal Frailty Metric Possible?mentioning
confidence: 99%